Influence of Periodontal Ligament Stem Cell-Derived Conditioned Medium on Osteoblasts - Solen Novello; Sylvie Tricot-Doleux; Agnès Novella; Pascal Pellen-Mussi; Sylvie Jeanne (MDPI AG, 2022)
Mesenchymal stem cells (MSC) are involved in the regeneration of various missing or compromised periodontal tissues, including bone. MSC-derived conditioned medium (CM) has recently been explored as a favorable surrogate for stem cell therapy, as it is capable of producing comparable therapeutic effects. This study aimed to evaluate the influence of periodontal ligament stem cells (PDLSC)-CM on osteoblasts (OB) and its potential as a therapeutic tool for periodontal regeneration. Human PDLSC were isolated and characterized, and CM from these cells was collected. The presence of exosomes in the culture supernatant was observed by immunofluorescence and by transmission electron microscopy. CM was added to a cultured osteoblastic cell line (Saos-2 cells) and viability (MTT assay) and gene expression analysis (real-time PCR) were examined. A cell line derived from the periodontal ligament and showing all the characteristics of MSC was successfully isolated and characterized. The addition of PDLSC-CM to Saos-2 cells led to an enhancement of their proliferation and an increased expression of some osteoblastic differentiation markers, but this differentiation was not complete. Saos-2 cells were involved in the initial inflammation process by releasing IL-6 and activating COX2. The effects of PDLSC-CM on Saos-2 appear to arise from a cumulative effect of different effective components rather than a few factors present at high levels.